Promising Efficacy of Benznidazole Nanoparticles in Acute Trypanosoma cruzi Murine Model: In-Vitro and In-Vivo Studies - Scalise, María L (2016)
Fil: Scalise, María L. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.